2011
DOI: 10.1017/s0025315411000464
|View full text |Cite
|
Sign up to set email alerts
|

Cetacean sightings and strandings: evidence for spatial and temporal trends?

Abstract: Cetacean species and their habitats are under threat and effective marine management mitigation strategies require knowledge and understanding of cetacean ecology. This requires data that are challenging and expensive to obtain; incidental sightings/strandings data are potential underused resources. In this study, incidental cetacean sightings (N = 6631) and strandings (N = 1856) in coastal waters of Cornwall, south-west Britain (1991 to 2008) were analysed for evidence of spatial and temporal patterns or tren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 43 publications
3
35
0
Order By: Relevance
“…The significance of these waters is also evident for dolphins and porpoises [81]–[82]. Environmental characteristics that influence the distribution of small cetaceans appear to differ geographically, and by season as we found in this study; nevertheless factors such as depth, slope, proximity to the coast, tidal state, and SST repeatedly surface as being important habitat features [22], [89], [92][101].…”
Section: Discussionsupporting
confidence: 57%
“…The significance of these waters is also evident for dolphins and porpoises [81]–[82]. Environmental characteristics that influence the distribution of small cetaceans appear to differ geographically, and by season as we found in this study; nevertheless factors such as depth, slope, proximity to the coast, tidal state, and SST repeatedly surface as being important habitat features [22], [89], [92][101].…”
Section: Discussionsupporting
confidence: 57%
“…(), which may have caused a change in grouping pattern (Arcangeli and Crosti , Pikesley et al . ) and displacement of individuals from the study area over time, as suggested earlier by Karczmarski et al . () and as seen in bottlenose dolphins off western Australia (Bejder et al .…”
Section: Discussionsupporting
confidence: 53%
“…The applied method provides a low-cost approach to obtain valuable long-term information for areas with limited or no specific monitoring effort over a wide geographic area (Delefosse et al, 2018). Although interpretation of nonsystematically collected data is difficult without measure of effort (Evans and Hammond, 2004), with stringent data filtering and quality control, valuable information can be obtained (Pikesley et al, 2012).…”
Section: Caveatsmentioning
confidence: 99%